Physiological and Behavioral Responses of Sohagi Ewe Lambs Exposed to Direct Sunlight Under Subtropical Climatic Conditions - M. Y. Elaref; G. M. Solouma; D. A. Abdel-latef (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study aimed to assess the ability of Sohagi ewe lambs to adapt to heat stress conditions during the summer season in arid regions of Sohag governorate, Egypt. Twenty-one Sohagi ewe lambs (9-11 months old and 25.55±2.69 kg average body weight) were divided into three equal groups. In the 1st group, ewe lambs were housed in an indoor barn and considered as control (DS0), while those in the 2nd and 3rd groups were daily exposed to direct sunlight in the outdoor barns for 4 hours (DS4) and 8 hours (DS8), respectively. Physiological, blood parameters, and daily behavioral activities of each animal in experimental groups were obtained and data were analyzed in a completely randomized design. Results showed that rectal temperature, respiration rate, and water consumption of Sohagi ewe lambs in DS4 and DS8 groups increased significantly (p<0.05) compared with those in the control one. The means of packed cell volume, hemoglobin, red blood cell counts, white blood cell counts, and neutrophil to lymphocyte ratio increased significantly (p<0.05) in ewe lambs in DS4 and DS8 than those in DS0. Glucose and total protein level of ewe lambs in DS4 and DS8 decreased significantly (p<0.05) compared with those in DS0, while potassium levels increased significantly (p<0.05), and sodium levels did not change. Daily behavioral observation illustrated that eating activities increased significantly (p<0.05) at night between sunset and sunrise in DS4 and DS8 than in DS0. Also, standing time in DS4 and DS8 groups increased significantly (p<0.05) compared with DS0. It could be concluded that the productive performance of ewe lamb groups exposed to direct sunlight was not affected. At the same time, physiological responses were significantly increased, reflecting the adaptability of Sohagi ewe lambs to heat stress under subtropical climatic conditions.